Pengaruh Struktur Kepemilikan terhadap Pengungkapan Corporate Social Responsibility dengan Board Independence sebagai Variabel Moderasi - Iit Gusti Sri Murni; Vanica Serly (Universitas Negeri Padang, 2024)
This research aims to determine how ownership structure influences Corporate Social Responsibility disclosure with Board Independence as a moderating variable. CSR disclosure is the dependent variable, while institutional, government and foreign ownership are the independent variables. The moderating variable is board independence. CSR disclosure is measured by dividing the disclosure weight by the number of disclosure items. Institutional ownership is measured by dividing institutional shares by total shares. Government ownership is measured by dividing government shares by total shares. Foreign ownership is measured by dividing foreign shares by total shares. Board Independence is measured by dividing the number of independent commissioners by the total board of commissioners. The data consists of annual and sustainability reports of mining companies in Indonesia listed on the Indonesia Stock Exchange for 2018-2022, with 28 companies as samples. Purposive sampling and moderated linear regression were used for data analysis. The research results show a negative impact of institutional and government ownership on CSR disclosure, while foreign ownership has a positive impact. Board Independence increases the relationship between institutional ownership and CSR disclosure, whereas government and foreign ownership do not.